PETA PERKEMBANGAN PENELITIAN MENGENAI PEMERINTAH AMERIKA SERIKAT DAN CHINA - Syamsul Bahri Abd. Rasyid (Jurnal Agregasi, 2022)
The United States and China are two superpowers that are often at odds. Researchers have also done much research on the comparisons between the two countries. This study describes the comparative development map between the United States and China in 2011-2020. The method used in this research is descriptive qualitative research, with the Scopus database as the data source. Based on the results of the analysis carried out, it was found that the research publications comparing the two countries were mostly done to the United States than to China, both in the number of documents, researchers, sources, affiliations, and countries. Furthermore, based on the analysis of VOSviewer and NVivo 12 plus, it was found that the most researched topics related to China government are topics around the economy, while health, politics, and public policy are the topics most frequently discussed in the United States government. . Future research needs to use PubMed and Web of Science as data sources, as well as the WordStat, VOSviewer and NVivo 12 plus software as data analysis tools.